Ergonomic Study in Trader's Area At Semat Sari Market, Tibuneneng Village - Farizi, Reza; Oktarina, Freta (Jurnal Teknologi dan Desain, 2025)
The market performance is intricately linked to the activities of traders, who play a central role in market dynamics. However, the extent of traders' freedom of movement is often overlooked in market environments. This study aims to evaluate the ergonomic quality of market spaces to assess the comfort of traders' movement. As a focal point, the study examined Semat Sari Market, the largest traditional market in Tibubeneng Village, Bali. The market is noteworthy as it serves the needs of two villages, leading to bustling operations. Spatial analysis was employed to analyze the flow of movement of traders within their stalls during work and rest. The research revealed a disparity between the space required by traders and the available space, negatively impacting the productivity of their work. Additionally, this situation can have repercussions on the psychological and physical well-being of traders.